(untitled) - Eisenstadt, Shmuel Noah (New Yersey, 1966)
Modernization of traditional societies series about the way quiet places have come alive, an to introduce at long last materials on the contemporary character of developing areas
Keywords: Social change,Thay đổi xã hội